2013
DOI: 10.1590/s1806-37132013000300007
|View full text |Cite
|
Sign up to set email alerts
|

Screening for F508del as a first step in the molecular diagnosis of cystic fibrosis

Abstract: OBJECTIVE: To determine the relevance of screening for the F508del mutation of the cystic fibrosis transmembrane conductance regulator gene as a first step in the genetic diagnosis of cystic fibrosis (CF) by associating the genotype with various clinical variables. METHODS: We evaluated 180 CF patients regarding the F508del mutation. The clinical data were obtained from the medical records of the patients and from interviews with their parents or legal guardians. RESULTS: Of the 180 patients studied, 65 (36.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
1
13
1
1
Order By: Relevance
“…The results of our study revealed that despite the high degree of miscegenation of the study population, with 96% non‐white patients, the initial investigation of only F508del mutation determined the genotype of approximately 30% of patients. This finding corroborates with the proposal of an initial investigation searching only for F508del mutation, as suggested for patients from the Brazilian southeast . In our population, subsequent investigation for G542X and 3120 + 1G>A mutations expanded the genotype knowledge to 50% of patients.…”
Section: Description Of the Cftr Mutations Screened In Patients With supporting
confidence: 91%
See 1 more Smart Citation
“…The results of our study revealed that despite the high degree of miscegenation of the study population, with 96% non‐white patients, the initial investigation of only F508del mutation determined the genotype of approximately 30% of patients. This finding corroborates with the proposal of an initial investigation searching only for F508del mutation, as suggested for patients from the Brazilian southeast . In our population, subsequent investigation for G542X and 3120 + 1G>A mutations expanded the genotype knowledge to 50% of patients.…”
Section: Description Of the Cftr Mutations Screened In Patients With supporting
confidence: 91%
“…This finding corroborates with the proposal of an initial investigation searching only for F508del mutation, as suggested for patients from the Brazilian southeast. 4 In our population, subsequent investigation for G542X and 3120 + 1G>A mutations expanded the genotype knowledge to 50% of patients. Thus, the establishment of a step wise protocol, with the research of only three mutations, can optimize the use of public health resources and increase the access to molecular diagnosis techniques.…”
Section: Cystic Fibrosis: Identification and Frequency Of Mutations Imentioning
confidence: 89%
“…In populations with a more homogenous CFTR mutation spectrum, targeted mutation panels are the most used genotyping strategy. In Brazil, Marson et al suggest the investigation of F508del for initial genetic screening of CF patients. Considering our finding of 38.8% of homozygosity for this mutation and an allelic frequency of 8.6‐48.7% of alleles in other Brazilian studies, this could be a cost‐effective strategy, avoiding the use of more expensive and complex molecular techniques in patients homozygous for F508del.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic Fibrosis (CF) (MIM: 219700) presents as phenotypic heterogeneity of the clinical manifestations that are modulated by cystic fibrosis transmembrane regulator (CFTR) mutations [1,2], the environment and modifier genes [3][4][5]. Our group has studied the clinical modulation of CF by candidate modifier genes that influence drug responses, the evolution of the lung and digestive disease in CF, and CF-related comorbidities [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%